Derrycarhoon a later Bronze Age copper mine in south-west Ireland - O'Brien, William 1961-; Hogan, Nick (BAR Publishing, 2022)
Derrycarhoon is the first copper mine from the later Bronze Age discovered in Ireland. This book presents the results of recent geoarchaeological survey and sample excavation of a small multi-period mine, with details of landscape setting, bedrock geology, mineralisation and palaeoecology. The recent history of mining and prospection at Derrycarhoon is examined, including the discovery in 1846 of so-called ?Danish Mines?, now dated c.1300-1000 BC. The technology and operation of that prehistoric copper mine is considered, as well as its significance for the supply of metal in later Bronze Age Ireland. The wider context is explored in relation to Bronze Age settlement in the region, with reference to ritual monuments and religious beliefs of the mining community. That local landscape of small farming communities was connected to trade networks at regional level, controlled by emerging hillfort chiefdoms at a time of growing militarism and pressures on metal supply in Ireland
Keywords: Kupferbergwerk; Archäologie; Bronzezeit; Irland; Copper mines and mining, Prehistoric / Ireland / Cork (County); Bronze age / Ireland / Cork (County); Excavations (Archaeology) / Ireland / Cork (County); Cuivre / Mines et extraction préhistoriques / Irlande / Cork (Comté); Fouilles (Archéologie) / Irlande / Cork (Comté); Bronze age; Copper mines and mining, Prehistoric; Excavations (Archaeology); Ireland / Cork (County); Aufsatzsammlung